Pengaruh Penggunaan Smartphone terhadap Perilaku Remaja - Usman, Usman; Maran, Yulida (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Cell phones have become one of the requirements for the wider community. Today all people in the world can be connected by a modern communication tool that is supported by the development of sophisticated media and modern communication. One of the media such as the mobile phone is now better known as